Cardiorespiratory Fitness and Hip Bone Mineral Density in Women: A 6-Year Prospective Study. Issue 2 (October 2014) - Tucker, Larry A.; Nokes, Neil R.; Bailey, Bruce W.; Lecheminant, James D.
Cross-sectional studies and short term interventions focusing on fitness and bone mineral density (BMD) are common. However, few investigations have studied the effect of fitness on BMD over an extended period of time. The present study was conducted to determine the extent to which cardiorespiratory fitness influences risk of BMD loss at the hip over 6 yr. A prospective cohort design was used with 245 healthy, middle-aged women. Hip BMD was assessed using dual energy x-ray absorptiometry. Calcium and vitamin D were measured using the Block Food Frequency Questionnaire. Menopause status was measured by a questionnaire. Results showed that fit and unfit women experienced similar changes in hip BMD over time. Specifically, unfit women experienced a non-significant 7% increased risk of losing hip BMD compared to their counterparts (RR = 1.07, 95% CI = 0.66, 1.73). Adjusting statistically for differences in age, initial body weight, and hip BMD, weight change, menopause status, calcium and vitamin D intake, and time between assessments had little effect on the relationship. Fitness level did not influence risk of hip BMD loss over time.